Public Awareness of the Implications of AI And Social Media Proliferation of Disinformation on Public Safety and Nigeria’s National Security - Lawal, Jibril Muhammed (African Journal of Stability and Development (AJSD), 2025)
The study examines public awareness of the implications of AI and social media in the proliferation of disinformation on public safety and national security in Nigeria. The study was anchored in Agenda Setting Theory. Data were generated from both primary and secondary sources. A sample size of 385 respondents from residents of FCT Abuja was interviewed using a questionnaire format. Respondents’ reactions range from strongly agree (SA), agree (A), disagree (DA) and strongly disagree (SDA). Data collected were analysed using tables of frequency and percentage for Objective One (1). The mean and standard deviations were applied for Objectives Two and Three using mean of 2.50 for Agree (A). The result of the findings showed that self-promotion, gaining more followers on social media and intention to create panic among the public are some of the factors that trigger disinformation. The study showed that disinformation creates panic in society, can lead to ethnic and religious bigotry and result in jungle justice in society. The dissemination of disinformation has been accelerated by the introduction and dominance of information and communication technologies, particularly social media, in the Twenty-First Century information environment. AI contributes to social media proliferation of disinformation, which has negative implications on public safety and national security. Specifically, the potential speed of AI-enabled cyber tools and the potential ability of a singular algorithm to spread disinformation are obvious. Criminals now have access to public information on social media. It makes bandits and terrorists gain popularity. It was recommended that the government should be realistic in the fight against insecurity in Nigeria by engaging the services of AI experts on all fronts.